Down-regulation of MMP-2 expression due to inhibition of receptor tyrosine kinases by imatinib and carboplatin in HNSCC - Schultz, Johannes D.; Rotunno, Sarah Elena; Erben, Philipp; Sommer, Ulrich; Anders, Clemens Frithjof; Stern-Sträter, Jens; Hofheinz, Ralf-Dieter; Hörmann, Karl; Sauter, Alexander (Oncology reports, 2011)
Squamous cell carcinoma of the head and neck (HNSCC) is the most common neoplasm arising in the upper aerodigestive tract. Unfortunately, the survival for this type of cancer has not improved significantly in the past 25 years. To enhance the survival rate multimodal therapy regimens have been set up. In these regimens chemotherapy plays a pivotal role in the majority of advanced cases. Transmembrane protein- tyrosine kinases (PTK) are fundamental elements of the signal transduction. In consequence, they might be promising targets for cancer therapy. Imatinib (STI 571) was originally designed to inhibit the BCR-ABL tyrosine kinase in chronic myeloid leukemia. But imatinib also has an inhibitory impact on the PTK receptor c-kit and on its PTK activity. Furthermore, growth and invasion of HNSCC are strongly influenced by the extracellular matrix (ECM). The ECM is altered by matrix metalloproteinases (MMP). In this study, we incubated different HNSCC cell lines with rising concentrations of imatinib and/or carboplatin. After an incubation time of up to 10 days, we evaluated c-kit, MMP-2 and MMP-14 by ELISA techniques and immunohistochemical methods. Especially the combination of 7.5 μmol carboplatin with 30 μmol imatinib resulted in a significant decrease in MMP-2 expression in all observed cell lines (p<0.05). We did not demonstrate a significant alteration in c-kit expression by imatinib and carboplatin. We observed an increase in apoptosis in HNSCC cells by the combination of the two observed chemotherapeutic drugs. In all cell lines tested, expression of c-kit and MMP could be demonstrated. Our results indicate that MMP-2 expression was suppressed in the presence of imatinib. Thus, imatinib may exert in part its inhibitory effect on malignant cell growth via the blockage of the signal transduction of PTK receptors. Further studies are warranted, especially one keeping in mind the moderate toxicity of imatinib.
Gesehen am 27.10.2022